РАЗРАБОТКА СУППОЗИТОРИЕВ, СОДЕРЖАЩИХ ПРОБИОТИЧЕСКИЕ ШТАММЫ LACTOBACILLUS (Experimental biology, 2015)
This article presents the results of the development of probiotic vaginal suppositories based on gelatin-glycerin, containing freeze-dried culture of lactobacillus L. salivarius and L. fermentum. Biological activity of a probioticcomplex studied in vitro, and the resulting biological product is promising as a new therapeutic and prophylactic complex for restoring the normal microflora оf a vagina of women.
Keywords: gelatin-glycerin; lactobacillus L.; salivarius and L.